Self healing wireless network - (:unkn) unknown (Kurukshetra, 2019)
not available
Keywords: Ad Hoc Network; Engineering and Technology,Computer Science,Computer Science Interdisciplinary Applications; Flat Routing; MANET; Routing Protocol; Self Healing Wireless Network; Wireless Network